2009
DOI: 10.1007/s00464-009-0793-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased mRNA expression of epidermal growth factor receptor, human epidermal receptor, and survivin in human gastric cancer after the surgical stress of laparotomy versus carbon dioxide pneumoperitoneum in a murine model

Abstract: The expression of EGFR, HER2, and survivin increased after each surgical procedure. However it was lower after CO(2) pneumoperitoneum than after laparotomy. This might be associated with changes in the chemosensitivity of the remnant cancer cells after surgery, supporting the use of minimally invasive surgery for cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…disease and incision-wounding modeled in our study. Interestingly, a recent animal study reported that expression of survivin in residual tumor tissues, taken as a surrogate marker of chemoresistance, began increasing within 6 h of surgery, peaked at post-operative day 2, and decreased to baseline levels by post-operative day 7 [ 29 ]. This suggested chemoresistance pattern during the immediate post-operative period is consistent with our finding of impaired cisplatin activity perioperatively vs. 7 days later.…”
Section: Discussionmentioning
confidence: 99%
“…disease and incision-wounding modeled in our study. Interestingly, a recent animal study reported that expression of survivin in residual tumor tissues, taken as a surrogate marker of chemoresistance, began increasing within 6 h of surgery, peaked at post-operative day 2, and decreased to baseline levels by post-operative day 7 [ 29 ]. This suggested chemoresistance pattern during the immediate post-operative period is consistent with our finding of impaired cisplatin activity perioperatively vs. 7 days later.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study used BALB/c mice to conduct the laparotomy and revealed an increase in the PI3K/ AKT-dependent tumor growth (Coffey, Wang, Bouchier-Hayes, Cotter, & Redmond, 2006). Meanwhile, increased expressions of EGFR and HER2 were reported to be involved in the enhanced tumor growth and chemoresistance induced by surgical stress from a laparotomy (Amin et al, 2010). In the current study, our results provided direct evidence to support that laparotomy promotes tumor progression in CT26 cells with the differentiation of tumor volumes in the laparotomy group and the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above five newly identified genes, we analyzed histamine receptor H1 (HRH1) since a previous study reported that this gene was overexpressed in gastric cancer cells, and the expression of this gene satisfied the above criteria (21). Moreover, three candidate marker genes [keratin 20 (CK20), epidermal growth factor receptor (EGFR) and carcinoembryonic antigen (CEA)], which have been reported to be promising markers for the detection of cancer cells, were further analyzed (11,13,22,23).…”
Section: Identification Of Up-or Down-regulated Genes In the Gastricmentioning
confidence: 99%